ESTIMASI PARAMETER MODEL DATA PANEL DINAMIK DENGAN KOVARIAT MENGGUNAKAN METODE ARELLANO-BOND - , Widya Irmaningtyas ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The dynamic panel data model with covariates is based on the concept of dynamics, when a variable is not only determined by other variables at the same time, but also determined by the variables in the previous time. The dynamic model contains lagged dependent variable, that correlated with the error term, as an explanatory variable. It causes the Ordinary Least Square (OLS) estimator is biased and inconsistent. Therefore, other estimation methods are needed, one of them is the Arellano-Bond method. This method is based on the Generalized Method of Moments (GMM), and produces an unbiased, consistent, and efficient estimator. As an application, a case study will be conducted on the effect of Direct Expenditure in the previous time, District Own Source Revenue, and General Allocation Fund on Direct Expenditure in the districts on the Java Island